Reclaiming the petition clause : seditious libel, "offensive" protest, and the right to petition the government for a redress of grievances - Krotoszynski, Ronald J., 1967- (Yale University Press, 2012)
Since the 2004 presidential campaign, when the Bush presidential advance team prevented anyone who seemed unsympathetic to their candidate from attending his ostensibly public appearances, it has become commonplace for law enforcement officers and political event sponsors to classify ordinary expressions of dissent as security threats and to try to keep officeholders as far removed from possible protest as they can. Thus without formally limiting free speech the government places arbitrary restrictions on how, when, and where such speech may occur.&#160.